Finite Element Analysis of Hybrid Composite Plate through Tensile Test - Zakaria, Mohd Faiz Farhan (IRC, 2021)
This project focuses on simulation study of hybrid composite plate by using the finite element analysis. Tensile test simulation is used to find out the tensile properties of the composite structures and the finite element model was designed to simulate the tensile test.